Berkeleyomyces rouxiae—A Pathogen Causing the Black Root Rot of Tobacco - Grażyna Korbecka-Glinka; Anna Trojak-Goluch; Diana Czarnecka (Pathogens)
Black root rot is a dangerous disease affecting many crops. It is caused by pathogens formerly known as Thielaviopsis basicola and then reclassified as two cryptic species, Berkeleyomyces basicola and B. rouxiae. The aim of this study was to perform species identification, morphological characterization, and pathogenicity tests for fungal isolates obtained from tobacco roots with black root rot symptoms in Poland. DNA sequences of the three regions (ITS, ACT, MCM7) were highly similar to the sequences of B. rouxiae deposited in the NCBI database. Phylogenetic analysis confirmed the assignment of the obtained isolates to this species. The cultures of four representative isolates (namely OT2, OT3, WPT7, WPT8) showed a similar structure and gray/brown color of the mycelium, although their growth rate varied from 3.8 to 5.1 mm/day depending on the isolate. The sizes of the endoconidia and chlamydospores showed a considerable variation, although they fit within ranges previously described for B. rouxiae. Pathogenicity tests performed on young tobacco plants grown in the inoculated peat substrate revealed differences among the four isolates. WPT7 demonstrated the lowest level of aggressiveness for tobacco. In contrast, the remaining three isolates caused severe disease symptoms and significantly reduced shoot and root dry weights of the susceptible cultivar Virginia Joyner. A parallel pathogenicity test performed on cultivar VRG 10TL confirmed the effectiveness of black root rot resistance derived from Nicotiana debneyi.